THE EFFECTIVENESS OF AQUATIC PHYSIOTHERAPY VERSUS HEALTH EDUCATION PROGRAM IN WOMEN WITH FIBROMYALGIA: A RANDOMIZED CLINICAL TRIAL (Anais do Congresso Brasileiro da Associação Brasileira de Fisioterapia Traumato-Ortopédica - ABRAFITO, 2019)
Introduction: Different treatments have been proposed for Fibromyalgia (FM), but only few studies have compared their effects on multiples outcomes over time. Objective: To investigate the effectiveness of aquatic physiotherapy (AP) versus a health education program (HEP) in a sample of women with FM. Methods: Forty-six women with FM were assigned to either AP (n=27) or HEP (n=19) groups in a blind randomized clinical trial lasting 11 weeks. Data of pain, fatigue, functional capability, anxiety, depression, and quality of sleep were collected at baseline, after six weeks and post intervention. Two-factor mixed-model analysis of variance (ANOVAs) were used to examine the effects of the treatment on each outcome variable, ?=0.05. (Ethical opinion - 687,895). Results: The AP and HEP interventions showed statistically significant intragroup differences on all outcome measures except reducing the pain. The group-by-time interaction for the mixed-model ANOVA was statistically significant only for functional capability [F(1.82,80.41)=31,99; p